Strategic Utilization of Google Sites to Support ICT Learning Management in Madrasah Education - Rahma Alia; Firdaus Annas (Journal of Educational Management and Strategy, 2025)
Information and Communication Technology (ICT) learning requires effective digital media utilization strategies to support flexible and adaptive learning management. However, studies examining strategic use of web-based platforms, particularly Google Sites, in the context of madrasah education remain limited. This study aims to describe the strategy of utilizing Google Sites as a digital learning medium to support ICT learning management at MA Asy Syarif Sidang Koto Laweh. This study employed a descriptive approach involving 15 students as participants. The implementation strategy included needs analysis, design of media structure and interface, organization of learning content such as materials, videos, and PDF documents, and integration of evaluation through Google Forms with automated scoring. Data were collected through observation and student response questionnaires and analyzed descriptively to illustrate both the process and outcomes of the implemented learning strategy. The results indicate that the use of Google Sites as part of a digital learning strategy supports more structured learning management, provides easy access across multiple devices, and enhances student engagement. Students demonstrated positive responses, particularly toward video-based materials and the automated evaluation system, which facilitated the learning process. This study focuses on the implementation of learning strategies rather than effectiveness testing. The findings offer practical contributions for teachers in designing web-based learning strategies and provide academic insights into the development of digital learning management and strategy in madrasah contexts.